PENGEMBANGAN E-BAHAN AJAR IPA BERBASIS PENDEKATAN SAINTIFIK DAN KETERAMPILAN PROSES SAINS PADA MATERI GETARAN DAN GELOMBANG - Nada Khoirun Nisa'; Rohmatus Syafi’ah; Rahyu Setiani (Jurnal Genta Mulia, 2025)
One of the factors that support success in learning science is teaching materials. Along with the times, the need for electronic teaching materials that can be accessed anytime and anywhere is considered practical. Achievement of science learning in the Merdeka Curriculum, one of which can be measured by science process skills. Science process skills have almost the same indicators as the scientific approach, so that both are suitable to be combined in science learning. This research aims to determine the level of validity and practicality of the developed teaching materials. The method used in this research is the development of the ADDIE model which includes 5 stages of development which include analysis, design, development, implementation, and evaluation. The results of the validation of electronic teaching materials product show a percentage score of 90,74% with very valid criteria and media experts 84,72% with very valid criteria. The results of the electronic teaching materials obtained practically results with score of percentage score of 93,3% with very practical criteria. Based on the results of this study, electronics teaching materials developed are valid and practical for use in learning science, especially on vibration and wave materials.